2008
DOI: 10.1353/mpq.0.0009
|View full text |Cite
|
Sign up to set email alerts
|

Order in the House! Associations among Household Chaos, the Home Literacy Environment, Maternal Reading Ability, and Children’s Early Reading

Abstract: The current study examines whether associations exist between household chaos and children's early reading skills, after controlling for a comprehensive battery of home literacy environment characteristics. Our sample included 455 kindergarten and First-grade children who are enrolled in the Western Reserve Reading Project. We go on to test whether these associations are moderated by maternal reading ability. Results suggest that the degree of household order is significantly and positively associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 76 publications
(82 reference statements)
1
50
1
Order By: Relevance
“…However, the room was comfortably arranged via a scripted protocol with prompts provided, highly conducive compared with oft-chaotic home environments experienced by low-SES families. 80 Our reading score reflected a single snapshot, and may not be representative of longer-term behavior, though household reading behaviors tend to be stable during the preschool period 81 and discrete observations are reliably used in assessment of the home environment, 82 including reading. 83, 84 Applying dialogic scoring criteria to mothers showing low mastery may be unrealistic.…”
Section: Discussionmentioning
confidence: 99%
“…However, the room was comfortably arranged via a scripted protocol with prompts provided, highly conducive compared with oft-chaotic home environments experienced by low-SES families. 80 Our reading score reflected a single snapshot, and may not be representative of longer-term behavior, though household reading behaviors tend to be stable during the preschool period 81 and discrete observations are reliably used in assessment of the home environment, 82 including reading. 83, 84 Applying dialogic scoring criteria to mothers showing low mastery may be unrealistic.…”
Section: Discussionmentioning
confidence: 99%
“…For example, family routines such as sleeping and eating schedules were not used. Prior research suggests that these types of routines may be important for children’s development (Johnson et al, 2008; Roy et al, 2004). These types of measures were not used in this study in an effort to not rely on parent subjective ratings and because many routines, like sleeping and eating schedules, are not stabilized for most young children until toddlerhood.…”
Section: Discussionmentioning
confidence: 99%
“…The indicators of family instability include residential mobility, the number of intimate adult relationships involving the primary caregiver, and the number of families with whom the child has lived (Ackerman, Kogos, Youngstrom, Schoff, & Izard, 1999). In contrast, family disorganization is indexed by ambient noise in the home/neighborhood, television watching in the home, household crowding, and disorganized family routines (Evans, Maxwell, & Hart, 1999; Johnson, Martin, Brooks-Gunn, & Petrill, 2008; Matheny, et al, 1995). Based on the extant literature, we propose that in a large, socio-economically and racially diverse rural sample and after controlling for child and primary caregiver covariates (e.g.…”
Section: The Current Studymentioning
confidence: 99%
“…A chaotic home environment also negatively impacts cognitive development even after controlling for SES (Hart, Petrill, Deater Deckard, & Thompson, 2007; Petrill, Pike, Price, & Plomin, 2004). Finally, studies have shown lower achievement among children in chaotic homes (Brody & Flor, 1997; Evans, 2006; Hanscombe et al, 2011; Johnson, Martin, Brooks-Gunn, & Petrill, 2008). These findings suggest that a chaotic home environment negatively affects school performance directly and indirectly.…”
Section: Introductionmentioning
confidence: 99%
“…The developmental propensity model (Lahey & Waldman, 2003; 2005) provides a set of candidate dispositions that allow the present study to extend prior work on dispositions related to reading achievement while also expanding the scope of outcomes that may be explained by the model. Finally, prior studies examining chaos in the home as it relates to general cognitive abilities (Hart et al, 2007; Johnson et al, 2008; Petrill et al, 2004) included an important control for SES. The only study showing the shared environmental underpinnings of the relationship between home chaos and school achievement (Hanscombe et al, 2011) did not include this control.…”
Section: Introductionmentioning
confidence: 99%